Kultur Meristem Mahkota Nanas (Ananas comosus (L.) Merr) dengan Penambahan EkstrakTauge dan Benzyl Amino Purin (BAP) - Riza Linda, Patrisia Rupina, Mukarlina, (Jurnal Protobiont, 2015)
The pineapple (Ananas comosus (L.) Merr) is one of the horticultural commodities with high economic and nutritional values. An alternative of the pineapple propagation is through in-vitro meristem culture. This research aimed to find out the effect of adding the bean sprout extract and Benzyl Amino Purine (BAP) on the growth of buds in the culture of crown tip meristem of pineapple as well as to findÂ  out the concentration of the bean sprout extract and BAP wich could produce the best growth in the culture of crown tip meristem of pineapple. This research was conducted for five months from January to May 2015. The research used a completely randomized design (CRD) with a factorial pattern which consisted of two factors, i.e. bean sprout extract (A) with a concertration of 0%(A0), 5%(A1), 10%(A2) and BAP (B) with a concentration of 0 M (B0), 10-5 M (B1), 10-6 M (B2) each factor was combined and each combination was repeated three times. The research findings showed that the treatment A0B1 had a significant effect on the number of buds and leaves. The average of buds produced was 5,44 and the average number of leaves was 25,78.